Variation in results release and patient portal access to diagnostic test results at an academic medical center - Matthew D Krasowski; Caleb V Grieme; Brian Cassady; Nicholas R Dreyer; Karolyn A Wanat; Maia Hightower; Kenneth G Nepple (Elsevier, 2017)
Background: Electronic health records (EHRs) are commonplace in industrialized countries. Many hospitals are granting their patients access to their medical information through online patient portals. In this report, we describe a retrospective analysis of patient access to diagnostic test results released through the patient portal (MyChart; Epic, Inc.) at a state academic medical center. Methods: We analyzed 6 months of data for anatomic pathology, clinical laboratory, and radiology test results to evaluate variations in results release (automated vs. manual) and subsequent patient access to the institutional patient portal. During this period, diagnostic test results were released for all patient encounters including inpatient units, outpatient clinics, and the emergency department. Results: Manual results release by providers before automated release time occurred most commonly in the outpatient setting. The highest rates of access of diagnostic test results occurred for outpatients (about 30% overall view rate), females (two times or more compared to males in nearly every age bracket), and 20-45-year-old. Access rates of diagnostic tests in the emergency department or inpatient units were <10% across all populations. Access of diagnostic test results was very low for 12-17-year-old, likely influenced by institutional policies limiting parental proxy access within this pediatric age range. Approximately 20% of outpatient laboratory results were viewed by patients within 8 h of release from the EHR to the patient portal and 10% within 2 h of release. Conclusions: Patient accessing of diagnostic test results were generally higher for females, outpatients, and 20-45-year-old. Approximately, 20% of outpatient results were viewed quickly by patients after release to the EHR.